Evaluation of financial performance of three coal companies in indonesia (case study of adaro, bayan, and indo tambangraya megah) - Sukma Putra, Anugrah; M. Daryanto, Wiwiek (The Indonesian Journal of Business Administration, 2019)
Abstract. Based on BP Statistical World Energy data in 2017, Indonesia is the country with the fifth largest coal production in the world with a total production is 271.6 million of ton of oil equivalent. In the last 8 years since 2009 China is the country with the largest production and consumption of coal in the world, but China's coal production cannot meet domestic consumption. Based on data in 2017 coal production in Indonesia is greater than its consumption, so that Indonesia becomes a coal exporting country. One of the destination countries for coal exports from Indonesia is China, but since 2013 coal consumption in China has continued to decrease. The impact of the reduction in coal consumption in China is the abundance of coal stock throughout the world, which causes coal prices to decline starting from 2013. In 2012 the price of coal was in the range of US $ 117 per metric ton, but in 2013 coal prices declined to be in the price range of US $ 85 per metric ton. In this study the author would like to know the impact of the decline in coal prices on financial performance and the effect of Fixed Asset Turnover and Return on Asset on the share prices of coal mining companies in Indonesia. The companies studied in this study were three coal mining companies that had the largest market capitalization in Indonesia, including: Adaro Energy (ADRO), Bayan Resources (BYAN), and Indo Tambangraya Megah (ITMG). The method used in this study is to analyze financial ratios such as liquidity, solvability, activity and profitability. Quarterly financial report data is taken from 2011 to 2017. After financial ratio analysis is carried out, validation with benchmark industries is carried out in the categories of Gross Profit Margin, Total Asset Turnover, Account Receivable Turnover, and Inventory Turnover. Data taken for the benchmark industry was taken from csimarket.com. To determine the effect of Fixed Asset Turnover and Return on Asset on stock prices, panel data regression analysis was conducted. To help processing panel data regression analysis the author uses Eviews software. The findings of this study show that ITMG is the best financial performance company during the period of 2011 to 2017 indicated by excellence in the three categories of financial ratios, namely solvability, activity, and profitability. Adaro is the second best financial company to excel in the liquidity category and the last is BYAN. The results of the standard industry benchmark validation for four financial ratios show that during the period 2011 to 2017 all categories are still below the industry standard. Fixed Asset Turnover and Return on Asset panel data regression on share prices show these two independent variables have a positive influence on share prices.Keywords: Coal Mining Companies, Financial Ratio, Panel Data Regression